Periodontal disease, tooth loss and colorectal cancer risk: Results from the Nurses' Health Study. Issue 3 (23rd November 2016) - Momen‐Heravi, Fatemeh; Babic, Ana; Tworoger, Shelley S.; Zhang, Libin; Wu, Kana; Smith‐Warner, Stephanie A.; Ogino, Shuji; Chan, Andrew T.; Meyerhardt, Jeffrey; Giovannucci, Edward; Fuchs, Charles; Cho, Eunyoung; et al.
Abstract : Periodontal diseases including tooth loss might increase systemic inflammation, lead to immune dysregulation and alter gut microbiota, thereby possibly influencing colorectal carcinogenesis. Few epidemiological studies have examined the association between periodontal diseases and colorectal cancer (CRC) risk. We collected information on the periodontal disease (defined as history of periodontal bone loss) and number of natural teeth in the Nurses' Health Study. A total of 77, 443 women were followed since 1992. We used Cox proportional hazard models to calculate multivariable hazard ratios (HRs) and 95% confidence intervals (95% CIs) after adjustment for smoking and other known risk factors for CRC. We documented 1, 165 incident CRC through 2010. Compared to women with 25–32 teeth, the multivariable HR (95% CI) for CRC for women with <17 teeth was 1.20 (1.04–1.39). With regard to tumor site, the HRs (95% CIs) for the same comparison were 1.23 (1.01–1.51) for proximal colon cancer, 1.03 (0.76–1.38) for distal colon cancer and 1.48 (1.07–2.05) for rectal cancer. In addition, compared to those without periodontal disease, HRs for CRC were 0.91 (95% CI 0.74–1.12) for periodontal disease, and 1.22 (95% CI 0.91–1.63) when limited to moderate to severe periodontal disease. The results were not modified by smoking status, body mass index or alcohol consumption. Women with fewer teeth, possibly moderate or severe periodontal disease, might be at a modest increased risk of developing CRC, suggesting a potential role of oral health in colorectal carcinogenesis. Abstract : What's new? Periodontal disease does not simply affect the mouth. It is also thought to increase systemic inflammation, trigger immune dysfunction, alter the microbiome and increase the risk of a number of cancers. Might it also increase colorectal cancer (CRC) risk? In this analysis of data from the Nurses' Health Study, the authors found that the risk of developing CRC increased by as much as 48% in women with periodontal disease. Cancer risk increased with the severity of tooth loss. These results suggest that oral health may affect factors involved in colorectal carcinogenesis.